Fixed and Variable Cost Principles for Financial Planning - Dhuyvetter, Kevin C. (My University, 1999)
The purpose of this guide is to explain how fixed and variable costs should be used in the production decision-making process, both in the short and long run.
MF1006_1999-10
Keywords: MF1006; Economics; MF